Developing a collaborative problem-solving instrument: A skills-based rubric in mathematics learning - Anjarsari, Elly; Juniati, Dwi; Masriyah, Masriyah (Edelweiss Applied Science and Technology, 2026)
Collaborative problem-solving is essential in mathematics education, yet many students face challenges due to a lack of effective assessment tools that adequately measure these skills. The existing approaches often overlook the integration of structured assessments, resulting in a significant gap in understanding how to cultivate and evaluate collaborative problem-solving abilities in students. This study aims to address these identified issues by developing a collaborative problem-solving instrument grounded in a skills-based rubric specifically for mathematics learning. Using a Research and Development (R&D) approach following the procedural framework of Borg and Gall, the study created a comprehensive assessment tool designed to enhance the measurement of collaborative problem-solving skills. Validation through Lawshe’s formula resulted in a content validity index of 0.99, confirming the instrument’s reliability. Practicality testing involved questionnaires distributed to middle school mathematics teachers, achieving a positive response rate of 92.46% in small-scale trials and an impressive 97.61% in large-scale field trials. These findings demonstrate the instrument’s effectiveness and practical applicability in classroom settings. The implications indicate that incorporating this structured assessment can significantly improve students’ collaborative problem-solving abilities, ultimately enhancing their engagement and learning outcomes in mathematics. Future research should explore the broader applicability of this instrument across various educational contexts and subjects to maximize its impact.